Evaluating the Obstacles to Implementing Construction Investment Projects in Iraq (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The impact of investment management has greatly increased over the past two decades as a result of the growing level of competition that exists between construction organizations and the shifting expectations regarding the nature and level of craftsmanship required for building projects. Because of this, in recent years it has been clear that companies that work in the construction industry require a complete system for the administration of investments.Since 2003, the building sector in Iraq has undergone a large amount of development, and the region's commercial linkages with the countries of other regions have undergone a substantial amount of advancement. Because Iraq was closed during this period, it needed a lot of investment for development projects.The primary goals of this study are to analyze and assess the obstacles that stand in the way of the implementation of investment construction projects in Iraq.